False-positive lung scans and radiotherapy. Issue 6013 (3rd April 1976) - Bateman, N T; Croft, D N
Abstract : It has been suggested that obliterative vasculitis in the lung might mimic pulmonary embolism on a ventilationperfusion scan. The combined scans of six patients with breast cancer who had undergone radiotherapy to the chest wall, which can induce pulmonary vasculitis, were therefore examined. Eleven of the 12 scans showed perfusion defects with ventilation-perfusion mismatch on the irradiated side. Special care is needed in interpreting the lung scans of patients who have received an appreciable tissue dose of radiation to the lungs; mismatch need not indicate pulmonary embolism.